2018
DOI: 10.18549/pharmpract.2018.02.1198
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric antimicrobial stewardship and safe prescribing-an assessment of medical staff knowledge and behaviour

Abstract: Objective:Determine baseline knowledge of antimicrobial stewardship, and safe prescribing among junior medical officers, monitor their level of participation in interactive education during protected teaching time and assess day-to-day prescribing behaviours over the subsequent 3-month period.Methods:A voluntary and anonymous survey of all non-consultant level medical officers was conducted with the use of an audience response system during mandatory face-to-face orientation sessions at a tertiary paediatric h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…An additional 15 citations were identified from the grey literature search for a total of 123 publications (figure 1). 13–135 Of the 123 studies, 64 were peer reviewed, 53 were conference proceedings and 6 were online documents (eg, reports).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional 15 citations were identified from the grey literature search for a total of 123 publications (figure 1). 13–135 Of the 123 studies, 64 were peer reviewed, 53 were conference proceedings and 6 were online documents (eg, reports).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 52 studies reported the prevalence of indication documentation 13–15 17 19 21 23 26–29 40 45–47 49 53 60 61 65 67 71 72 74 75 78 82 83 87 89 91 92 97 100–102 106 108 109 109 110 112 114 115 117 124–129 135. The median reported prevalence of indication documentation was 75%; however, there was a wide range across studies from 4% to 100% of antimicrobial orders with an indication documented, with an IQR of 51%–85%.…”
Section: Resultsmentioning
confidence: 99%
“…Phytochemicals can inhibit peptidoglycan synthesis, damage microbial membrane structures modify bacterial membrane surface hydrophobicity and modulate quorum-sensing. 42 With increasing antibiotic resistance in recent years, the potential of new plantderived antibiotics is under investigation.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…These were Qd, OD, U, mcg, trailing zeros or failure to include a leading zero when the dose is less than a one. [9] Audits in a Sri Lankan hospital, showed use of following error-prone abbreviations - μg (microgram), mcg (microgram), u (units), cc (cubic centimeter), OD (once a day), @ sign, d (days/daily), m (morning) and n (night) - at a rate of 17.4%, 0.1%, 1.9%, 0.2%, 0.2%, 4.9%, 23.5%, 4.4% and 15.8% respectively among all prescriptions reviewed. [10] In our study, overall incidence of error prone abbreviations before intervention was 47.5%.…”
Section: Discussionmentioning
confidence: 99%
“…These were Qd, OD, U, mcg, trailing zeros or failure to include a leading zero when the dose is less than a one. [9] Audits in a Sri Lankan hospital, showed use of following error-prone abbreviations - prescriptions reviewed. [10] In our study, overall incidence of error prone abbreviations before intervention was 47.5%.…”
Section: Post-intervention Incidence Of Epasmentioning
confidence: 99%